Girl haven - Sturges, Lilah (Oni Press, 2021)
"Three years ago, Ash's mom left home and never returned, leaving behind a husband and child and a shed full of mystical curiosities related to the all-girl fantasy world she'd created as a child -- Koretris. One day Ash invites a new group of friends from Pride Club over, and they try one of the spells to enter Koretris. To their amazement, they're all transported to a magical realm filled with human-sized talking animals who are fiercely protective of their world and are ready to fight to protect it. But if Koretris is real, why is Ash there? Everyone has always called Ash a boy -- shouldn't the spell have kept Ash out? And what does it mean if it let Ash in?"--Provided by publisher